Phase IV study on the use of benzydamine mouthwash in radiation-induced oral mucositis in patients with head and neck cancer - Bossi, Paolo; Tellone, Valeria; Di Loreto, Giorgio; Fioravanti, Sara; Salvatori, Enrica; Comandini, Alessandro (Frontiers in Oncology, 2024)
Introduction Oral mucositis (OM) is a main side effect of treatment for head and neck cancer (HNC) and causes severe pain, reduces quality of life, and may interrupt HNC treatment. This study assessed the activity and feasibility of benzydamine mouthwash in the prevention and treatment of radiation-induced OM in patients with HNC during radiation therapy (RT). Methods This phase IV, international, open-label, single-group study conducted from December 2021 to September 2022. In total, 89 patients were enrolled across seven centers in Hungary and Poland. Patients used benzydamine mouthwash at home two to three times daily. Data were collected during clinical visits at baseline (V0, start of RT) and then weekly for seven visits (V1–V7). The safety population and the modified intention-to-treat (m-ITT) analysis sets contained 89 patients; the per protocol (PP) analysis set contained 67 patients. Results The m-ITT set was 80.9% male; mean age was 61.4 years. At baseline, 73.0% of patients had stage T3-T4, 23.6% had stage T1-T2, 61.8% had stage N2-N3, and 34.9% had stage N0-N1. Within the m-ITT population, 33.7% (n=30) responded to treatment (NRS < 5) during the study. The PP set responded similarly (29.9%). Most patients were treatment compliant (n=77; 86.5%). OM severity was assessed using the WHO OM grading scale. No patients had severe mucositis at baseline or V1. At V7, 34.1% had mild mucositis, 45.1% had moderate mucositis, 15.9% had severe mucositis, and 1.2% had life-threatening mucositis. In total, 26 patients (29.2%) developed severe mucositis during the study period (V2–V7). From V1 to V4, one patient reported hospitalization due to mucositis or associated complications, two patients at V5, three patients at V6, and four patients at 7. Discussion This was the first study to assess feasibility of a treatment for radiation-induced OM with benzydamine mouthwash in patients with HNC. Treatment compliance suggested that benzydamine was well tolerated in patients with moderate to severe mucositis. Benzydamine’s anesthetic and anti-inflammatory properties might have reduced pain, which potentially influenced patients’ compliance with RT. Few patients in the study required hospitalization for OM or an associated complication, suggesting that benzydamine might improve healthcare resource utilization.